LITERACKA I FILMOWA REFLEKSJA NAD TOTALITARYZMEM − NA PRZYKŁADZIE POWIEŚCI KLAUSA MANNA MEFISTO ORAZ JEJ ADAPTACJI FILMOWEJ W REŻYSERII ISTVÁNA SZABÓ - Płusa, Czesław (Acta Neophilologica, 2013)
Klaus Mann’s novel Mephisto and its film adaptation directed by István Szabó put the reader in a mood for reflective judgments about human behavior which grows on the ground of the totalitarian system. The spectrum of Mann’s novel and Szabó’s film is made up by the world of the Third Reich’s culture, where the actual reality, specific human fates, biographies and events are determined by the conformism as well as the heroism of fight. Klaus Mann’s novel and István Szabó’s film are mutually complementary in their disparate modes of expression and cognition of man. The film adaptation encompasses the elements impossible to represent in the text of the novel. In contrast with image, language as the basic device of literature is helpless in the face of a rich diversity of direct individual experiences. For language is reflective by nature, aiming to capture a whole (Kierkegaard). The cinematic picture performs a function that is complementary to language, which fails as a direct medium of the dynamism of the characters’ inner lives. The film is able to depict what is passed over by the novel. Describing Höfgen’s existential and spiritual situation, both the novel and the film reveal his inner downfall. There is no escaping the affinity with the stigma of the evil – a source of negative evaluation in the 20th century. This phenomenon is not self-acting but conditioned by the sociopolitical context in which the individual gets tangled up. In conclusion, the author quotes other examples from European literature, which expose the mechanics of the evil summoning up the powers of the Antichrist, common to the various epochs.